2015
DOI: 10.1128/aac.01363-15
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Raoultella ornithinolytica Coproducing IMP-4 and KPC-2 Carbapenemases in China

Abstract: bWe report here the emergence of seven IMP-4-producing Raoultella ornithinolytica isolates obtained from one patient. All isolates carried the bla IMP-4 carbapenemase gene, five isolates also carried bla SHV-12 , four contained bla TEM-1 , and one contained bla OXA-1 . Notably, the R. ornithinolytica isolate Ro25724 also expressed Klebsiella pneumoniae carbapenemase (KPC)-2. The bla KPC-2 gene was located on a Tn3-Tn4401 integration structure on a plasmid of ϳ450 kb. This is the first description of the coexis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 24 publications
0
60
1
1
Order By: Relevance
“…B-lactamase genes had been identified on a couple of Raoultella spp. big plasmids and megaplasmids before (bla IMP-4 and bla KPC-2 on 450 kb plasmid, bla NDM-1 on 41 kb and 100 kb plasmids, bla OXA-48 on 63 kb or bla KPC-2 40 kb plasmid) (Sun et al 2015;Zheng et al 2015;Yao et al 2017). However, this is the first observation of a bla gene on a very small plasmid in Raoultella spp.…”
Section: Discussionmentioning
confidence: 64%
“…B-lactamase genes had been identified on a couple of Raoultella spp. big plasmids and megaplasmids before (bla IMP-4 and bla KPC-2 on 450 kb plasmid, bla NDM-1 on 41 kb and 100 kb plasmids, bla OXA-48 on 63 kb or bla KPC-2 40 kb plasmid) (Sun et al 2015;Zheng et al 2015;Yao et al 2017). However, this is the first observation of a bla gene on a very small plasmid in Raoultella spp.…”
Section: Discussionmentioning
confidence: 64%
“…[52][53][54][55] Nonetheless, a few strains of R. ornithinolytica generating simultaneously different types of beta-lactamase (TEM, SHV, KPC and OXA) were described. 42,56 The first case of co-existence of bla KPC-2 and bla IMP-4 carbapenemase genes in the genus Raoultella was reported by Zheng et al (2015) in a 13-year-old male patient with postoperative infection after an orthopedic surgery. 57 The R. ornithinolytica strain was identified in this report by 16S rRNA sequencing and antimicrobial susceptibility was determined with VITEK ® 2 and Etest strips (Bioméreux, France) on 7 samples collected from the wound fluid and necrotic tissue.…”
Section: Virulence and Resistancementioning
confidence: 99%
“…42,56 The first case of co-existence of bla KPC-2 and bla IMP-4 carbapenemase genes in the genus Raoultella was reported by Zheng et al (2015) in a 13-year-old male patient with postoperative infection after an orthopedic surgery. 57 The R. ornithinolytica strain was identified in this report by 16S rRNA sequencing and antimicrobial susceptibility was determined with VITEK ® 2 and Etest strips (Bioméreux, France) on 7 samples collected from the wound fluid and necrotic tissue. 57 The isolated strains were reported as resistant to all antimicrobials except ciprofloxacin.…”
Section: Virulence and Resistancementioning
confidence: 99%
“…10 Enterobacteriaceae species produced bla IMP-4 , but E. cloacae was the most frequent (60.4%, 29/48) and possessed bla IMP-4 on conjugatable HI2 (22/29 or L/M (7/29) plasmids demonstrating a plausible mechanism for bla IMP-4 proliferation throughout the region [Sidjabat 2015]. A pediatric patient in China in June 2014 had seven closely related bla IMP-4 producing Raoultella ornithinolytica isolated from an infected surgical wound, including the first observation of an R. ornithinolytica in China producing bla IMP-4 and bla KPC-2 [Zheng 2015]. Analysis of mobile genetic elements surrounding MBLs in Enterobacteriaceae collected in Spain from February to July 2009 found that all 14 bla VIM-1 genes were associated with class 1 integrons but a mixture of genetic backgrounds (2/14 bla VIM-1 , IncU and 12/14 unidentified plasmid type) [Zamorano 2015].…”
Section: Impmentioning
confidence: 99%